2007
DOI: 10.1002/pros.20643
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐Gallate suppresses early stage, but not late stage prostate cancer in TRAMP mice: Mechanisms of action

Abstract: The attenuation of the AR, the down-regulation of potent growth factor IGF-1, modulation of inflammation biomarkers, and decrease in the MAPK signaling may contribute to the reduction in cell proliferation and induction of apoptosis and hence provide a biochemical basis for EGCG suppressing PCa without toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 55 publications
5
91
0
3
Order By: Relevance
“…Consistent with the fact that NECa originated from VP independently of AR, suppressing AR signaling in DLP was one of the important mechanisms underlying the chemopreventive effect of SSA, both in vivo and in vitro [14]. Similar to our strategy, Harper et al gave TRAMP mice (C57BL/6) water containing 0.06% EGCG starting at 5 WOA and dissected DLP and VP carefully when mice were euthanized at 12 WOA [50]. They found that EGCG significantly reduced the incidence of HG-PIN (Grade 3) from 100% to 17% in the VP of TRAMP mice but did not have a protective effect in DLP.…”
Section: Effects Of Chemopreventive Agents On Prostate Carcinogenesissupporting
confidence: 70%
See 1 more Smart Citation
“…Consistent with the fact that NECa originated from VP independently of AR, suppressing AR signaling in DLP was one of the important mechanisms underlying the chemopreventive effect of SSA, both in vivo and in vitro [14]. Similar to our strategy, Harper et al gave TRAMP mice (C57BL/6) water containing 0.06% EGCG starting at 5 WOA and dissected DLP and VP carefully when mice were euthanized at 12 WOA [50]. They found that EGCG significantly reduced the incidence of HG-PIN (Grade 3) from 100% to 17% in the VP of TRAMP mice but did not have a protective effect in DLP.…”
Section: Effects Of Chemopreventive Agents On Prostate Carcinogenesissupporting
confidence: 70%
“…Besides the effect of androgen deprivation therapy (ADT) on the progression of PCA by surgical castration of TRAMP mice [41,42], the effects of many agents with chemopreventive potential including green tea [26,43], NSAIDs [44,45], flutamide [46], retinoic acid [47], vitamin E analog [48], genistein [24,49], epigallocatechin-3-gallate (EGCG) [50], silibinin [23,51], dietary restriction [52] and immunotherapy [53,54], have been studied using this model. While most of the publications reported anti-cancer effects of their test compounds, El Touny et al showed that feeding TRAMP mice (TRAMP-FVB) with a diet containing 0.25% genistein from 12 to 20 WOA induced an aggressive progression of PCA, as evidenced by a 16% increase in the number of WD and PD prostates, coinciding with a 70% incidence of pelvic lymph node metastases as opposed to 0% in the control group [49].…”
Section: Effects Of Chemopreventive Agents On Prostate Carcinogenesismentioning
confidence: 99%
“…production, has been observed in many different tumors [48][49][50][51]. In TRAMP mice who received, 0.06% EGCG in tap water ad libitum for 7 weeks starting at weaning, a reduction of the HG-PIN incidence was observed, concomitantly with a significant downregulation of iNOS [52].…”
Section: Effects Of Gtcs On Nos Productionmentioning
confidence: 89%
“…TRAMP mice fed with green tea polyphenols exhibited significant inhibition of IGF-1 and restoration of IGFBP-3 with marked delay in CaP progression [16]. In addition, down-regulation of AR and insulin-like growth factor-1, modulation of inflammation biomarkers, and decrease in the MAPK signaling seen in EGCG treated mice may contribute to the reduction in cell proliferation and induction of apoptosis by EGCG and provide a biochemical basis for suppressing CaP without overt toxicity [17,18]. In addition, testosterone mediated induction of ornithine decarboxylase, an important contributor of CaP development, is inhibited by green tea polyphenols both under in vitro and in vivo situations [19].…”
Section: Green Teamentioning
confidence: 98%